Aero-propulsive performance assessment approach to boundary layer ingestion aircraft - Moirou, Nicolas G. M. (Cranfield University, 2023)
A promising solution towards more sustainable and efficient aircraft propulsion relies upon the ingestion of the boundary layer flow that develops around the airframe. Amongst the plethora of concepts, the propulsive fuselage concept appears to be the most pragmatic configuration, as a direct adoption of conventional tube-and-wing aircraft, which has an additional propulsor integrated around its tail. Nonetheless, there is a lack of consensus in the quantification and interpretation of the performance of such vehicles. Long-established momentum-based bookkeeping schemes break down as their underlying assumptions do not hold true in highly-integrated airframe-propulsion systems. Alternative approaches have been brought forth by considering holistically the aircraft to evaluate its performance and decompose its aerodynamic forces. Notably, energy- and exergy-based approaches improve one’s understanding on the cause and effect of boundary layer ingestion mechanisms but require high computational demands with dense grids. In sought of a universal approach, energy- and momentum-based methods are used together in this work to quantify the coupled aerodynamic performance of boundary layer ingestion aircraft. The strengths of near-field momentum integrations are coupled with more informative energy-based flow assessments. The design space of a propulsive fuselage aircraft is explored via CFD after a reduction of its modelling to an axi-symmetric partial assembly of the fuselage and propulsor. With variations in the thruster position along the tail, its flow passage through the fan and pressure rise, and exhaust design, best performance is achieved with a concept where the propulsor lies at 90% of the fuselage chord, for a fan hub radius of 30% of the fuselage radius, that ingests around 43% of the boundary layer mass-flow, and applies a pressure rise of 1.29, to generate around a third of the total propulsive force requirement whilst savings 11% of fuel relative to a short-to-medium range aircraft propelled by state-of-the-art turbofans. The reasons for such savings are detailed with a first-of-its-kind fully energetic flow decomposition which aims at attributing boundary layer ingestion benefits to changes in propulsor design.
Keywords: boundary layer ingestion; aircraft concepts; aerodynamics; propulsion integration; computational fluid dynamics; near-field momentum